Impact of globalisation on environment and energy consumption - Narandaran, Yasmin Yashodha (2019)
Globalisation, particularly from the perspective of economic globalisation is notably the most profound and debated issues that have a ubiquitous influence on the environment and energy consumption. The distributional impact of globalisation has affected the environment and led to the rise of unsustainable energy consumption patterns attributed to demographic pressures and rapidly evolving technological frontiers across the globe. Presently, limited literature has incorporated globalisation variables from the revised KOF Globalisation Index (2018) to examine its impact on the environment and energy consumption. Thus, this study intends to investigate the impact of the segregated trade and financial globalisation policies that encompasses distinctive dimensions of economic globalisation on environmental degradation, environmental sustainability and energy consumption. This study utilised the two-step system generalised-method-of-moments (GMM) methodology framework to examine the three research objectives of this study. The first objective investigates the impact of globalisation on carbon emission per capita, based on a panel of 143 countries (full sample) spanning over a period from 1994 – 2014. The full panel is further segregated into the low income and lower-middle income (LLMI) sample comprising 63 countries and the upper-middle-income, and high income (UMIHI) sample consisting of 80 countries. For the second and third research objective, the impact of globalisation on the ecological footprint of consumption per capita and energy consumption per capita were examined respectively, based on a panel of 137 countries spanning over a period from 1994 – 2014. The full panel was further segregated into low income and lower-middle income (LLMI) comprising 62 countries and the upper-middle-income, and high income (UMIHI) consisting of 75 countries. Findings from the first objective have illustrated that existing trade and financial globalisation policies have led to the degradation of the environment, from the perspective of the full panel, the LLMI panel and the UMIHI panel. Present globalisation policies have not been able to advocate sustainable economic development via technology transfers and failed to execute effective trade and investment restrictive policies to deter the establishment of pollution-emitting industries, particularly amongst nations within the LLMI panel. From the second objective, the findings postulate that existing globalisation policies have led to unsustainable practices pertaining to livestock production, deforestation and overfishing attributed to intensified agricultural production and energy consumption which threatens environmental sustainability. Across all the examined panels of study, it is evident that existing globalisation policies have caused a decline in ecological reserves, as natural resources have been exploited beyond sustainable scales.